Prevalence of Neuropsychiatric Symptoms in Mild Cognitive Impairment and Alzheimer's Disease, and its Relationship with Cognitive Impairment - Fernandez-Martinez, M.; Molano, A.; Castro, J.; J. Zarranz, J. (Current Alzheimer Research, 2010)
Objective The study aimed to describe the prevalence of Neuropsychiatric symptoms (NPS) in Alzheimer's disease (AD), amnestic mild cognitive impairment (MCI) and controls using the 12-item Neuropsychiatric Inventory (NPI) and to analyze the relationships between neuropsychiatric symptoms with specific neuropsychological tests.Patients and methods; We prospectively studied 485 patients from the Memory Unit in Cruces Hospital (Spain), 344 met the criteria of NINCDS-ADRDA for probable AD (99 were classified as mild and 245 as moderate-severe), 91 for MCI and 50 were controls. Mini-mental State Examination (MMSE) and CDR (Clinical Dementia Rating) were used to evaluate global cognitive function and to classify the severity of cognitive impairment. The neuropsychological test battery included memory test, verbal fluency, visuoespatial skills and daily living scales. The 12-items Neuropsychiatric Inventory (NPI) version was used to assess neuropsychiatric symptoms. All patients underwent a neuroimaging study (CT scan and/or MRI). Patients were not treated with antidementia or psychotropic drugs. Results;Apathy and depression were more prevalent NPS in moderate-severe AD (78.4% and 44.1%, respectively), mild AD (64.6% and 41.4%, respectively) and MCI (50.5% and 33%, respectively) patients than in controls (6% and 8%, respectively). The prevalence and the mean scores of all symptoms increased along the severity of the disease, except for sleep and appetite disorders. In patients with mild AD a relationship was found between the presence of NPS and RDRS-2 scale (p = 0.003); and between NPS and RDRS-2 (p = 0.029) and SS-IQCODE scales (p = 0.039) in moderate-severe patients.Conclusions; NPS were more prevalent in AD and MCI patients than in controls. In AD and MCI patients apathy and depression were the most prevalent NPS. The prevalence and the mean scores of all symptoms gradually increased along the severity of the disease, except for sleep and appetite disorders. We have no found a relationship between neuropsycological test and the presence of NPS, but in patients with mild and moderate-severe AD there is a relationship with daily living scales.
Keywords: mild cognitive impairment